Microbial distribution in the root canal system after periapical lesion induction using different methods - Tanomaru, Juliane Maria Guerreiro [UNESP]; Leonardo, Mario Roberto [UNESP]; Tanomaru-Filho, Mário [UNESP]; da Silva, Léa Assed Bezerra; Ito, Izabel Yoko (FapUNIFESP (SciELO), 2008)
The aim of this study was to evaluate the microbial distribution in the root canal system after periapical lesion induction in dogs' teeth using different methods. Fifty-two root canals were assigned to 4 groups (n=13). Groups I and II: root canals were exposed to the oral cavity for 180 days; groups III and IV: root canals were exposed for 7 days and then the coronal openings were sealed for 53 days. The root apices of groups I and III were perforated, while those of groups II and IV remained intact. After the experimental periods, the animals were euthanized and the anatomic pieces containing the roots were processed and stained with the Brown & Brenn method to assess the presence and distribution of microorganisms. The incidence of microorganisms at different sites of the roots and periapical lesions was analyzed statistically by the chi-square test at 5% significance level. All groups presented microorganisms in the entire root canal system. A larger number of microorganisms was observed on the root canal walls, apical delta and dentinal tubules (p<0.05), followed by cementum and cemental resorption areas. In spite of the different periods of exposure to the oral environment, the methods used for induction of periapical periodontitis yielded similar distribution of microorganisms in the root canal system.
Keywords: Endodontics; Microorganisms; Periapical periodontitis; Pulp cavity; Pulp necrosis; coloring agent; diagnostic agent; animal; bacterium; cementum; dentin; dog; endodontics; growth, development and aging; instrumentation; methodology; microbiology; mouth; pathology; time; tooth disease; tooth periapical disease; tooth pulp; tooth root; ultrastructure; Animals; Bacteria; Coloring Agents; Dental Cementum; Dental Pulp Cavity; Dentin; Dogs; Mouth; Periapical Periodontitis; Pulpectomy; Root Canal Obturation; Root Canal Preparation; Root Resorption; Time Factors; Tooth Apex